Mejoramiento del Proceso de Gestión de Artes Gráficas en el “Subproceso de impresión de modelos” de la Agencia Geocuba - Bárbara, Rosabal-Palma; Medel-González, Frank (EASI: Engineering and Applied Sciences in Industry, 2022)
The paper shows a proposal to enhance the model-impression management process in a graphic art company. The authors identified some negative factors affecting variables from production to commercialization processes as the number of customers complaints, and the lack of transportation facilities and technology. Procedures and scientific techniques, like expert advice, bibliographic revision, customer survey, documentary analysis and quality management methods, were applied to improve the efficiency and quality of the impression process.
Keywords: Business Process Management; Process modeling; Processes Simulation